PREDIKSI KEBANGKRUTAN CV. BATUBARA MAS ABADI DI SAMARINDA - -, Lisa Cinthia (EKONOMIA, 2014)
The company was founded with the hope of generating a profit to be able to survive in the long term infinite. The company uses profits generated to develop and maintain the continuity of the company. Often companies that have been operating for a certain period forced to disband because of a business failure. One way to do company for the company to survive, by interpreting or analyzing financial statements. The problem in this study is